The Effect of the Application of Contextual Teachinglearning Toward Students’ Listening Ability of Grade XI at MAN 2 Tanjung Karang in 2014 - Eka Wahyuni Kartika (Bandar Lampung University (UBL), 2014)
The objective of this research was aimed to find out the effect of the application of contextual teaching learning toward students’ listening ability of grade XI at MAN 2 Tanjung Karang, academic year 2013 – 2014. in learning a language, the first step will be listening. In order to learn a language well, she or he must be a competent listener. Data were collected by incorporating two pre-tests and two post-tests in experimental group and control group. Treatment using the application of CTLwas administered in experimental group, while control group received traditional teaching (TT). Data analysis was attempted using t-Test for two group design.Result indicated that p-value 1% = 2, 64, 5% = 1,99 , and t-value = 5, 53. It means p-value is smaller than t-value. Therefore, hypothesis testing showed that null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. The writer concluded that the application of using contextual teaching learning more effective than traditional teaching.